PERBANDINGAN PENGUBURAN KERANDA KAYU DI TANA TORAJA DENGAN KERANDA KAYU DI SABAH (BORNEO)-KALIMANTAN - Akin Duli; Stephen Chia Ming Soon; Muhammad Husni (Balai Arkeologi Provinsi Sulawesi Selatan, 2011)
Asal-usul tentang budaya keranda kayu di kawasan Tana Toraja belum diketahui dengan pasti. Namun berdasarkan studi perbandingan dengan kawasan lainnya di Asia Tenggara seperti kawasan Sabah di Borneo-Kalimantan, dapat memberikan gambaran tentang adanya persamaan bentuk dan bahkan asal-usul dari keranda kayu Toraja. Dengan menggunakan metode deskripsi dan perbandingan tipologi, dapat diketahui adanya persamaan bentuk maupun tata letak, sehingga dapat diasumsikan bahwa keranda kayu di kedua kawasan tersebut, berasal dari satu asal-usul budaya yang sama, atau kemungkinan besar keranda kayu Toraja berasal dari kawasan Sabah (Borneo)-Kalimantan pada masa lampau. The origins of culture in the wood coffins in Tana Toraja region is not known with certainty. However, based on comparative studies with other regions in Southeast Asia as the region of Sabah on Borneo-Kalimantan, can provide a snapshot of the similarities of form and even the origin of the wooden coffin Toraja. By using the method of description and comparison of typology, typology can be known the equation as well as the layout, so it can be assumed that the wooden coffin in both regions, derived from a single origin of the same culture, or is likely to Toraja wood coffin comes from the region Sabah (Borneo)-Kalimantan in the past.